Assessment of Clinical Complications in Patients with Implant-Supported Dentures - Erkinova Sevinch Shokhimardonovna; Hadzhimuradov Burkhan Ravshanovich (Scientific Trends, 2024)
Partial or complete absence of teeth is a serious problem for both dentists and their patients. Implantation of missing teeth is a reliable way to restore incomplete dentition, significantly improving the quality of life of patients. Despite the wide range of implant-based prosthetics, existing methods and materials do not exclude cases of early and late complications. The premise for the use of orthopedic structures based on dental implants is the high aesthetic, functional, articulatory aspects of their use. However, an analysis of modern literature sources shows that orthopedic rehabilitation of patients with missing teeth by storing crowns based on dental implants has a fairly high percentage of complications. Tooth loss can negatively affect the aesthetics of the face, affect the functions of speech and chewing.